Half‐Cell and Full‐Cell Applications of Highly Stable and Binder‐Free Sodium Ion Batteries Based on Cu3P Nanowire Anodes. (23rd May 2016) - Fan, Mouping; Chen, Yu; Xie, Yihao; Yang, Tingzhou; Shen, Xiaowei; Xu, Na; Yu, Haiying; Yan, Chenglin
Abstract : Sodium‐ion battery (SIB) is especially attractive in cost‐effective energy storage device as an alternative to lithium‐ion battery. Particularly, metal phosphides as potential anodes for SIBs have recently been demonstrated owing to their higher specific capacities compared with those of carbonaceous materials. Unfortunately, most reported metal phosphides consist of irregular particles ranged from several hundreds nanometers to tens of micrometers, thus delivering limited cyclic stability. This paper reports the sodium storage properties of additive‐free Cu3 P nanowire (CPNW) anode directly grown on copper current collector via an in situ growth followed by phosphidation method. Therefore, as a result of its structure features, CPNW anode demonstrates highly stable cycling ability with an ≈70% retention in capacity at the 260th cycle, whereas most reported metal phosphides have limited cycle numbers ranged between 30 and 150. Besides, the reaction mechanism between Cu3 P and Na is investigated by examining the intermediate products at different charge/discharge stages using ex situ X‐ray diffraction measurements. Furthermore, to explore the practical application of CPNW anode, a pouch‐type Na + full cell consisting of CPNW anode and Na3 V2 (PO4 )3 cathode is assembled and characterized. As a demonstration, a 10 cm × 10 cm light‐emmiting diode (LED) screen is successfully powered by the Na + full cell. Abstract : An in situ growth followed by phosphidation method is applied to fabricate additive‐free Cu3 P nanowire (CPNW) anode with highly stable cyclic behavior toward sodium over 260 cycles. Sodiation/desodiation mechanism of CPNW is investigated by examining the intermediate products at different charge/discharge stages using ex situ X‐ray diffraction measurements. Na + full cell application is demonstrated by pairing CPNW anode with Na3 V2 (PO4 )3 cathode.